Subconjunctival Injection of Transdifferentiated Oral Mucosal Epithelial Cells for Limbal Stem Cell Deficiency in Rats. (March 2021) - Xiao, Yu-Ting; Xie, Hua-Tao; Liu, Xin; Duan, Chao-Ye; Qu, Jing-Yu; Zhang, Ming-Chang; Zhao, Xin-Yue
Rat limbal niche cells (LNCs) have been proven to induce transdifferentiation of oral mucosal epithelial cells (OMECs) into corneal epithelial-like cells termed transdifferentiated oral mucosal epithelial cells (T-OMECs). This investigation aimed to evaluate the effect of subconjunctival T-OMEC injections on alkali-induced limbal stem cell deficiency (LSCD) in rats. LNCs were cocultured with OMECs in the Transwell system to obtain T-OMECs, with NIH-3T3 cells serving as a control. Subconjunctival injection of single T-OMEC or OMEC suspension was performed immediately after corneal alkali injury. T-OMECs were prelabeled with the fluorescent dye CM-DiI in vitro and tracked in vivo. Corneal epithelial defect, opacity, and neovascularization were quantitatively analyzed. The degree of corneal epithelial defect (from day 1 onward), opacity (from day 5 onward), and neovascularization (from day 2 onward) was significantly less in the T-OMEC group than in the OMEC group. Cytokeratin 12 (CK12), pigment epithelium–derived factor, and soluble fms-like tyrosine kinase-1 were expressed at a higher rate following T-OMEC injection. Some CM-DiI-labeled cells were found to be coexpressed with CK12, Pax6, and ΔNp63α in the corneal epithelium after subconjunctival injection. Subconjunctival injection of T-OMECs prevents conjunctival invasion and maintains a normal corneal phenotype, which might be a novel strategy in the treatment of LSCD: